2016
DOI: 10.5937/intrev1604025g
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organizational culture on the ultimate performance of a company

Abstract: The tendency towards the realization of profits, efficiency and growth of companies, emphasized in capitalism, has encouraged organizations to think about what is common for successful companies and what differentiates them from those considered unsuccessful. Thus, the organizational culture has become one of the most common themes in management theory and practice.As a means of regulating the conduct of an organization's members, organizational culture permeates all of its factors, manifesting itself as a cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
1
6
0
2
Order By: Relevance
“…These interview remarks are in line with [23,25,38]. One may argue that, some of these studies are outdated; however, many earlier and current studies are in congruence with these findings such as; [12,16,18,40,25,6]…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These interview remarks are in line with [23,25,38]. One may argue that, some of these studies are outdated; however, many earlier and current studies are in congruence with these findings such as; [12,16,18,40,25,6]…”
Section: Discussionsupporting
confidence: 78%
“…On a broader perspective, [16] asserts that, dimensions of culture are central to all aspects of organizational life as organizational culture forms the integrative means of regulating the behavior of the organization's members and permeates all its activities, as a specific catalyst for growth and development of the organization. Leithy [17] on local and multinational companies' employees located in Cairo, Egypt showed that both workrelated attitudes and work behavior are related to organizational performance.…”
Section: Introductionmentioning
confidence: 99%
“…Culture plays an important role in the success or failure of any organisation (Gavric, Sormaz & Ilic 2016). Organisational culture acts as an inner strength to the company and should be aligned with the business strategy to ensure success and competitiveness (Eaton & Kilby 2015;Ghannay & Mamlouk 2015).…”
Section: Strategic Intent and Success Orientationmentioning
confidence: 99%
“…Para Gavric et al (2016) la importancia de la cultura se refleja en la actitud generalmente aceptada de que una verdadera cultura organizacional conduce al éxito, a una mayor eficiencia y eficacia de las operaciones de la compañía y al crecimiento y desarrollo. La medición del rendimiento es importante para la gestión efectiva de las empresas (Taouab y Issor, 2019).…”
Section: Cultura Organizacionalunclassified